Non-linear relationships between central cardiovascular variables and V.O2 during incremental cycling exercise in endurance-trained individuals - Vella, C. A.; Robergs, R. A. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of this study was to examine the relationships between the central cardiovascular variables (cardiac output, stroke volume and heart rate) and oxygen uptake (V.O2) during continuous, incremental cycle exercise to maximal aerobic capacity (V.O2max). Methods: Twenty-one moderately to highly trained males (n=19) and females (n=2) participated in the study. A baseline maximal exercise test was performed to measure V.O2max. Following the initial V.O2max test, cardiac output was measured (CO2 rebreathing technique) at rest and 3 times during each of 4 exercise trials (2 submaximal tests to 90% V.O2max and 2 maximal tests). Stroke volume and arteriovenous O2 difference were calculated using standard equations. Results: Significant non-linear relationships were found between all central cardiovascular variables and V.O2 (P<0.01). A plateau in cardiac output at V.O2max was identified in 3 subjects. Stroke volume plateaued at an average of 37±12.5% of V.O2max in 18 subjects and increased continuously to V.O2max in 3 subjects. The arteriovenous O2 difference progressively increased to V.O2max in 17 subjects and revealed a plateau response in 4 subjects. Conclusion: Our data suggest that there is a significant non-linear relationship between the central cardiovascular variables and V.O2 during incremental exercise to V.O2max. Furthermore, depending on the person, V.O2max may be limited by cardiac output (evidence of cardiac output[Q] plateau) or peripheral factors (continued increase in Q).